2007
DOI: 10.2355/isijinternational.47.95
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mould Flux Properties on Thermo-mechanical Behaviour during Billet Continuous Casting

Abstract: During continuous casting mould powder forms a pool of liquid flux which infiltrates into the solidifying shell/mould gap and forms a flux film containing liquid and/or solid layers. Subsequent crystallisation of the film results in the formation of an air gap at the mould wall. An air gap can also be formed by the shrinkage of the solidified shell. In practise, no air gap is formed by shell shrinkage in the upper mould since molten flux will flow immediately into and fill any gap formed. However, in the lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 27 publications
2
39
0
Order By: Relevance
“…At the exit of the mold, the thickness of the air gap is approximately 0.5-0.6 mm, and the thermal resistance is about 7.5 × 10 − 4 − 9 × 10 − 4 m 2 ·K/W. These results are in accordance with other published research 11) and verify the reliability of the model. As the heat transfer coefficients of the air gap and solid slag are relatively small, they severely hinder heat transfer lubrication between the mold and slab; therefore, it is of great significance to predict the non-uniform distribution of the air gap and slag films exactly.…”
Section: Thermal Resistance Of the Liquid Slag Filmsupporting
confidence: 80%
“…At the exit of the mold, the thickness of the air gap is approximately 0.5-0.6 mm, and the thermal resistance is about 7.5 × 10 − 4 − 9 × 10 − 4 m 2 ·K/W. These results are in accordance with other published research 11) and verify the reliability of the model. As the heat transfer coefficients of the air gap and solid slag are relatively small, they severely hinder heat transfer lubrication between the mold and slab; therefore, it is of great significance to predict the non-uniform distribution of the air gap and slag films exactly.…”
Section: Thermal Resistance Of the Liquid Slag Filmsupporting
confidence: 80%
“…[2] Thus, the mold fluxes strongly affect the final surface quality of the slab and involve with the formation of casting defects, such as longitudinal cracking, star cracking, oscillation marks, mold wear, and breakouts. [3] During continuous casting, the liquid mold flux infiltrates into the shell/mold gap and solidifies on the water-cooled copper mold forming complex amorphous and crystalline structures due to the large temperature gradient distribution between the steel shell and copper mold. [4] The mold flux is usually composed of two to three layers, depending upon the cooling rate and its chemical compositions, i.e., a liquid layer next to the steel shell, a solid glassy layer against the mold wall, and a crystallized layer in between, or sometimes just a liquid and a solid crystalline layer.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Normally, it is stated that the gap arises because the crystalline phase has a higher density than the glass, and therefore crystallization results in shrinkage of the solid flux layer. [10,11] In an investigation carried out to determine the surface roughness of solidified mold fluxes, it was found that this was in the range of 10 to 30 lm, when the crystalline phase precipitated; [12] this surface roughness was claimed to agree with the calculated thickness of the air gap assumed to form between the mold and the solidified slag layer. Furthermore, it was disclosed that the surface roughness of mold powder slags for casting medium-carbon steels is larger than that of mold slags used for low-carbon steels.…”
Section: Introductionmentioning
confidence: 86%